Macroalgae Community Structure in The Waters of Budo Village, Wori District, North Minahasa Regency - Ellu, Dwiko Yonathan; Kepel, Rene C.; Tombokan, John L.; Wantasen, Adnan S.; Mantiri, Rose O.S.E.; Lohoo, Anneke V. (JURNAL PESISIR DAN LAUT TROPIS, 2026)
This study aims to examine the community structure of macroalgae in the waters of Budo Village, Wori District, North Minahasa Regency. Data collection was conducted on June 26, 2025, during the lowest low tide using the Line Transect method with a quadrat sampling technique (1 m × 1 m) along three 50 m transect lines. Environmental parameters including temperature and salinity were measured. The study identified 13 macroalgae species comprising 4 Chlorophyta species (Caulerpa sertularioides, Bornetella oligospora, Halimeda macroloba, H. opuntia), 5 Phaeophyta species (Padina australis, Turbinaria decurrens, T. ornata, Sargassum polycystum, S. ilicifolium), and 4 Rhodophyta species (Amphiroa fragilissima, Tricleocarpa fragilis, Hydropuntia edulis, Portieria hornemannii). Total macroalgae density was 16.93 ind/m² with Turbinaria ornata as the dominant species (species density 5.467 ind/m²; relative density 32.28%). The Shannon-Wiener diversity index indicated moderate diversity (H’ = 2.051), Simpson’s dominance index was low (D = 0.169), and the evenness index was high (E = 0.80). Environmental conditions with temperatures of 30–31°C and salinity of 33‰ supported macroalgae growth. Overall, the coastal ecosystem of Budo Village is in a stable condition without significant ecological stress. Keywords: macroalgae, density, diversity, dominance, evenness Abstrak Penelitian ini bertujuan untuk mengkaji struktur komunitas makroalga di perairan Desa Budo, Kecamatan Wori, Kabupaten Minahasa Utara. Pengambilan data dilaksanakan pada 26 Juni 2025 saat kondisi surut terendah de ngan menggunakan metode Line Transect dengan teknik sampling kuadrat (1 m × 1 m) pada tiga garis transek sepanjang 50 m. Parameter lingkungan yang diukur meliputi suhu dan salinitas. Hasil penelitian menemukan 13 spesies makroalga yang terdiri atas 4 spesies Chlorophyta (Caulerpa sertularioides, Bornetella oligospora, Halimeda macroloba, H. opuntia), 5 spesies Phaeophyta (Padina australis, Turbinaria decurrens, T. ornata, Sargassum polycystum, S. ilicifolium), dan 4 spesies Rhodophyta (Amphiroa fragilissima, Tricleocarpa fragilis, Hydropuntia edulis, Portieria hornemannii). Total kepadatan makroalga adalah 16,93 ind/m² dengan Turbinaria ornata sebagai spesies dominan (kepadatan jenis 5,467 ind/m²; kepadatan relatif 32,28%). Indeks keanekaragaman Shannon-Wiener menunjukkan kategori sedang (H’ = 2,051), indeks dominansi Simpson rendah (D = 0,169), dan indeks kemerataan tinggi (E = 0,80). Kondisi lingkungan dengan suhu 30–31°C dan salinitas 33‰ mendukung pertumbuhan makroalga. Secara keseluruhan, ekosistem pesisir Desa Budo berada dalam kondisi stabil tanpa tekanan ekologis yang signifikan. Kata kunci: makroalga, kepadatan, keanekaragaman, dominansi, kemerataan, Minahasa Utara